Integration of Renewable Energy and Blue Carbon Ecosystems for Coastal Climate Change Mitigation and Adaptation in Indonesia's Oil and Gas Industry - Susandi, Armi; Wijaya, Aristyo Rahadian; Ihsan, Mustafid; Nugroho, Ahmad Wirantoaji; Zulfikar, Muhammad Rafid (Journal of Earth and Marine Technology (JEMT), 2024)
This study investigates the potential of integrating renewable energy and blue carbon ecosystems for coastal climate change mitigation and adaptation in Indonesia's upstream and downstream oil and gas industry. The urgency for the integration is also discussed, including climate change mitigation, energy security, technological innovation, social and environmental justice, and long-term planning and resilience. The study uses Army Design Methodology to identify the key challenges and opportunities of integrating renewable energy and blue carbon ecosystems. The findings suggest that the integration of renewable energy and blue carbon ecosystems can play a crucial role in coastal climate change mitigation and adaptation, particularly in Indonesia's oil and gas industry. The paper concludes with recommendations for further research and policy development in this area.